SISTEM INFORMASI PERPUSTAKAAN PADA SMP NEGERI 52 BANDUNG - Annisa Sari Saputri; Mia Fitriawati (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2017)
Library in 52 Junior High School Bandung has a very important role for educational facilities as a service that supports the teaching and learning process. Library Information System at 52 Junior High School Bandung has a function as a support the needs of students and also can facilitate the library staff in performing tasks related to data processing the data and presentation reports that have had constraints. The research method used is descriptive research method. While the supporting software used to create Information Systems Library in 52 Junior High School Bandung is NetBeans IDE 8.0, XAMPP v3.2.2 and using the Java programming language. With the Library Information System at 52 Junior High School Bandung is expected to facilitate the work of staff in the library activities and to be implemented to assist the performance of library staff.